A concept in flux and starved of the metaphysical: desecularizing emotion - Mobayed, Tamim (Frontiers in Psychology, 2024)
This conceptual article examines the case for conducting an Islamic analysis of the emotions. It might seem a peculiar area to examine; what would be the need to analyze such a universal psychological concept through the lens of a particular religion?2 Three points are used to argue for this endeavor. To begin with, this article sheds light on the relative instability of the term itself; there is yet no universally agreed upon definition of what the emotions are, and which human processes fall under the remit of their functions (and which do not). Underlying this point is the idea that given the concept is still being defined, there is merit in contributing to the discussion, particularly given the relative absence of metaphysics from the discussion. While debates continue about the nature and function of emotions, what is not disputed is their importance to humans.3 Secondly, specificities relating to the emotions and how they have been conceptualized are considered. This section delves into the way in which variable factors, such as culture, language, and worldview, influence how emotions are experienced. The overarching point argued for here is that the way emotions are experienced, and even which emotions are experienced, are shaped by factors that are not consistent across space and time. Accordingly, different worldviews will formulate different 'emotional palates' and 'emotional ideologies'. By extension, different groups of people will understand and engage with emotions differently.Thirdly, a broader discussion ensues pertaining to the nature of science, psychology, and their relationship with secularity. This discussion includes reflection on the idea that secularism and scientific materialism have been "discovered" and are therefore neutral. Accordingly, understandings of emotions to have emerged from the Academy, and contemporary psychology, are likely value-laden. This section also looks at the origins of science in order to determine whether science is inherently atheistic or areligious, and therefore antagonistic to a religious worldview. A range of other specificities pertaining to how the emotions have been conceptualised, such as their relational core, their interaction with moral faculties, and their enmeshment with what is important to the individual, are considered as well.